Implementation of Flashcards Media in Learning Hijaiah Letters for Early Childhood - Amani, Aisyah Melynia; Robbani, A. Syahid; Yunianti, Fitria Sari (Universitas Ahmad Dahlan, 2024)
Learning media is a tool used to help the teaching and learning process become more effective and enjoyable. One of the fun and interesting learning media is flashcardss. This study aims to determine how the implementation of flashcards and supporting factors and inhibiting factors of flashcards media in learning hijaiah letters in early childhood at the Rumah Tahfidz Balita Ahmad Dahlan. This study uses a field case study research type that uses a qualitative descriptive method. In this study, the use of qualitative descriptive methods was chosen as an approach that can be used to analyze the role of flashcards media in learning hijaiah letters in early childhood. The subjects of this study included the principal, ustadzah and students of the Sibyani class at Rumah Tahfidz Toddler Ahmad Dahlan, with the object of research in the form of flashcards learning media. Using the Miles and Huberman model technique in determining data analysis. Data collection techniques with observation, interviews, and documentation. The results of this study are that Rumah Tahfidz Toddler Ahmad Nganjuk uses flashcardss as the main media for learning hijaiah letters. In the learning process, there are two stages, namely the preparation and implementation stages. Some supporting factors and inhibiting factors are supporting factors including 1) Teacher competence, 2) Facilities and infrastructure, 3) Utrujah method as a learning method, 4) Cooperation between teachers and parents. As for inhibiting factors, namely 1) Children's characteristics. 2) Students do not follow learning effectively.